2017
DOI: 10.15296/ijwhr.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Educational Software and Booklet on Knowledge Level Regarding Labor Pain Management: A Randomized Controlled Clinical Trial

Abstract: IntroductionMore than 90% of the stress and anxiety during pregnancy is associated with birth process (1). Labor pain as biological, psychological and social phenomenon, has complex and multiple relationships with many psychological, cultural and racial dimensions and the economic status of human. Therefore, seeking strategies to reduce or eliminate such pain has always been a demand of most mothers and relevant people involved in this domain. Lack of awareness and fear of unknown issues related to pregnancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, some studies evaluated the greater effectiveness of multimedia compared to booklet method in pregnant women's knowledge of pain management [14], nursing students' learning practical skills [15], patients with type II diabetes [16], and training patients undergoing arthroscopy in which multimedia education leads to more effective learning [17]. According to experts, adding images to the text in booklets can contribute to learning among students [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies evaluated the greater effectiveness of multimedia compared to booklet method in pregnant women's knowledge of pain management [14], nursing students' learning practical skills [15], patients with type II diabetes [16], and training patients undergoing arthroscopy in which multimedia education leads to more effective learning [17]. According to experts, adding images to the text in booklets can contribute to learning among students [18].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have been conducted to compare the multimedia and conventional methods such as booklets and indicated that multimedia plays a more signi cant effect than conventional education on knowledge, skill, and self-e cacy [12], depression and anxiety [13], the severity of pain, overdramatization of pain, and coping with pain [14], as well as knowledge and skills among the patients [15].…”
mentioning
confidence: 99%
“…According to Claus et al (2017), studies using booklet media showed their effectiveness in increasing short and long-term knowledge. An RCT study conducted by Abbasi et al (2017) involving 153 pregnant women proved that educational software and booklets were equally effective in increasing pregnant women's knowledge about labor pain management.…”
Section: Discussionmentioning
confidence: 99%
“…In further research, booklet media can be given during counseling so that there is a significant increase in knowledge and attitudes. Abbasi et al (2017), in an RCT study of 126 gestational diabetes patients, conducted face-to-face training using a booklet. The results showed that the intervention could improve the health of mothers and babies.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, if the learners are ready to participate in the discussion or the subject is understandable to them, training can gain an acceptable success [ 23 ]. Another method of training is through booklet which usually can be used when there is not sufficient number of trainers [ 24 ]. Given the special role of mothers in caring for their adolescent girls, sexual health and regarding so far no study has been done to compare the effect of different training methods on mothers’ awareness, attitude and self-efficacy about sexual health care of id adolescent girls, so, the present study was conducted to compare the effect of two educational interventions on mothers’ awareness, attitude and self-efficacy about the sexual health care of id adolescent girls.…”
Section: Introductionmentioning
confidence: 99%